2017
DOI: 10.1093/biolinnean/blx130
|View full text |Cite
|
Sign up to set email alerts
|

Feathers for escape: the transition from juvenile to adult in red-legged partridges (Alectoris rufa)

Abstract: Almost all birds use their fight feathers as a means of escaping predators, and their specific design is adapted to their individual circumstances. For example, Galliform birds use a fast, explosive, noisy takeoff to startle a predator. Their legs, wings and feathers must work together to create a strong propulsive force and loud, rhythmic sound. Partridges in a group initiate escape simultaneously, even though individuals in the flock differ in size and experience, as well as in age and sex resulting in feath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…As a consequence, changes in species proportions [ 54 ] and increasing potential to escape predation [ 55 ] could condition survival. Wing models in age-sex classes of partridges were better linked to juvenile females than other age-classes, because juvenile females have less mass and a larger surface/mass index than the other age-sex classes [ 39 ]. Thus, females have a better conformation than males, and juveniles than adults, for flying but not for walking-running; for walking-running, males and adults have an advantage due to their larger size [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, changes in species proportions [ 54 ] and increasing potential to escape predation [ 55 ] could condition survival. Wing models in age-sex classes of partridges were better linked to juvenile females than other age-classes, because juvenile females have less mass and a larger surface/mass index than the other age-sex classes [ 39 ]. Thus, females have a better conformation than males, and juveniles than adults, for flying but not for walking-running; for walking-running, males and adults have an advantage due to their larger size [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 ). In previous studies we found scaling between mass and body length, wing length [ 38 ], 8th, 9th 10th feather length, and surface index (body length x wing length) [ 39 ], with bivariate approximations of multivariate phenomena. Scaling reflects physical constraints and natural selection based on a conflict between terrestrial and aerial locomotion due to multiobjective optimization [ 11 ] of body structure.…”
Section: Methodsmentioning
confidence: 99%
“…Among the few studies that have assessed variation between age classes in wing shape in nonpasserine birds, one carried out on western Sandpipers Calidris mauri (Charadriiformes), a migratory species, found the same pattern as in passerines, with juveniles having more rounded wings than adults (Fernández & Lank, 2007). In turn, two other studies, of Red-Legged Partridges Alectoris rufa (Galliformes, sedentary) and European Turtle Doves Streptopelia turtur (Columbiformes, migratory) found the opposite pattern (nadal et al, 2017;Cabodevilla et al, 2018). This illustrates that the pattern of wing shape differences between juvenile and adult passerines cannot be generalised to all species and bird orders.…”
Section: Introductionmentioning
confidence: 98%
“…The most important variable that makes this heterogeneity possible is wing shape (Hickman et al, 2008). wing morphology is directly linked to bird activity and behaviour (del Hoyo et al, 1997;Lockwood et al, 1998;Burns & ydenberg, 2002;Swaddle & Lockwood, 2003) and thus provides information about the relative importance of different activities and behaviours in the life of birds (Pérez-Tris & Tellería, 2001;nadal et al, 2017;Cabodevilla et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation